2021
DOI: 10.1063/5.0054048
|View full text |Cite
|
Sign up to set email alerts
|

Liquid structure and dynamics in the choline acetate:urea 1:2 deep eutectic solvent

Abstract: We report on the thermodynamic, structural and dynamic properties of a recently proposed Deep Eutectic Solvent (DES), formed by choline acetate and urea at the stoichiometric ratio 1:2, hereinafter indicated as acetaline. Acetaline, although melting at ca. 40 °C, can be easily supercooled in its liquid state at sub-ambient conditions. The existence of a crystalline phase has been detected, together with the glass-liquid transition at -50 °C. Synchrotron high energy X-ray scattering experiments provide the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
4
24
0
Order By: Relevance
“…29 Another similarity between the two systems is that there is almost no change in the signals of choline (the only exception is the CH 2 OH group, as discussed in the following), meaning they are not particularly affected by the addition of water. This is not surprising given the minor role of choline cations in the intermolecular network of nonhydrated ChCl:U and ChOAc:U, 49 and the fact that water is not expected to form specific interactions with its (hydrophobic) alkyl portion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Another similarity between the two systems is that there is almost no change in the signals of choline (the only exception is the CH 2 OH group, as discussed in the following), meaning they are not particularly affected by the addition of water. This is not surprising given the minor role of choline cations in the intermolecular network of nonhydrated ChCl:U and ChOAc:U, 49 and the fact that water is not expected to form specific interactions with its (hydrophobic) alkyl portion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, the carbonyl carbon of acetate is the site showing the most intense downfield shift, suggesting a strong competition with urea CO in the hydrated DES. Indeed, the oxygen acceptor of acetate was found to be involved in the shortest and strongest H-bond interactions in neat ChOAc:U, 49 and its major role is even strengthened upon the addition of water. Dynamic Scenario: Changes in Local and Long-Range Mobilities upon Dilution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, a special issue of the Journal of Chemical Physics titled "Chemical Physics of Deep Eutectic Solvents" was launched, to which the reader is referred for more information on DESs. [10][11][12][13][14][15][16][17][18][19] DESs and ionic liquids (ILs) are often regarded as superior solvents compared to volatile organic compounds (VOCs) due to a negligible vapor pressure at room temperature. 2,5,6,20 Such a low vapor pressure would limit the emission and loss of the DESs into the atmosphere and may facilitate the removal of solutes from DESs by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…27,45,51,69 Previously, it has been demonstrated that the distributions of relaxation rates for molecules which reside in different local environments in organized media like ILs are responsible for dynamic heterogeneity in that medium. 44,[69][70][71] We note here that Biswas and co-workers have demonstrated that decoupling of the rotational diffusion of a solute from the viscosity of the medium is caused by the dynamic heterogeneity of the medium. 44,50,51 Thus, the more the deviation of p from unity, the more the viscosity-diffusion decoupling and the more the dynamic heterogeneity of the medium.…”
Section: Pccp Papermentioning
confidence: 72%